Mitochondriomics of Clarias Fishes (Siluriformes: Clariidae) with a New Assembly of Clarias camerunensis: Insights into the Genetic Characterization and Diversification - Piyumi S. De Alwis; Shantanu Kundu; Fantong Zealous Gietbong; Muhammad Hilman Fu’adil Amin; Soo-Rin Lee; Hyun-Woo Kim; Ah Ran Kim (Life, 2023)
The mitogenome of an endemic catfish Clarias camerunensis was determined from the Cameroon water. This circular mitogenome was 16,511 bp in length and comprised 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a single AT-rich control region. The heavy strand accommodates 28 genes, whereas the light strand is constituted by ND6 and eight transfer RNA (tRNA) genes. The C. camerunensis mitochondrial genome is AT biased (56.89%), as showcased in other Clarias species. The comparative analyses revealed that most of the Clarias species have 6 overlapping and 11 intergenic spacer regions. Most of the PCGs were initiated and terminated with the ATG start codon and TAA stop codon, respectively. The tRNAs of C. camerunensis folded into the distinctive cloverleaf secondary structure, except trnS1. The placement of the conserved domains in the control region was similar in all the Clarias species with highly variable nucleotides in CSB-I. Both maximum likelihood and Bayesian-based matrilineal phylogenies distinctly separated all Clarias species into five clades on the basis of their known distributions (South China, Sundaland, Indochina, India, and Africa). The TimeTree analysis revealed that the two major clades (Indo-Africa and Asia) of Clarias species might have diverged during the Paleogene (≈28.66 MYA). Our findings revealed the separation of Indian species (C. dussumieri) and African species (C. camerunensis and Clarias gariepinus) took place during the Paleogene, as well as the South Chinese species (Clarias fuscus) and Sundaland species (Clarias batrachus) splits from the Indochinese species (Clarias macrocephalus) during the Neogene through independent colonization. This pattern of biotic relationships highlights the influence of topography and geological events in determining the evolutionary history of Clarias species. The enrichment of mitogenomic data and multiple nuclear loci from their native range or type locality will confirm the true diversification of Clarias species in African and Asian countries.